Efeito in vitro de extratos de sementes de plantas da amazônia sobre streptococcus mutans - Diaz , Stephanie Oliveira Quiñónez (2009)
Dental caries is an oral disease that affects more than 50% of the Brazilian population. Streptococcus mutans is the leading cause of dental caries (tooth decay). The chemical control of dental plaque can be done as a prophylactic or therapeutic treatment, using products of plant origin, with the advantage of having lower rate of side effects, while delivering same quality and efficiency, when compared to synthetics. Seeds of 32 plant species were selected, most in accordance with their availability on the Germplasm Bank of legumes and non-legumes at the National Institute for Research in the Amazon (INPA), in Brazil. Some species are not native to the Amazon forest, but they are well adapted well in the region. The seed extracts were tested for their ability to inhibit the growth of Streptococcus mutans in culture media containing soya peptone, as well as to remove dental plaque by using extracted teeth from humans. The chlorhexidine, the most used and effective antimicrobial in dentistry, was used as positive control in all tests. The seeds extracts of the following species have presented halos of S. mutans microorganism growth inhibition, behaving like chlorhexidine diluted to 0.2%, 0.1% and 0.05%: Solanum sessiliflorum (cocona), Cariniana micrantha (brown capuchin monkey), Hymenaea courbaril (locust tree), Zygia cauliflora (jarandeua), Mucuna urens (cow-icht plant), Parkia pendula (acacia male) and Ricinus communis (castor bean - extracts of green and mature seeds). The Abelmoschus esculentus (ochro), Basella rubra (malabar nightshade), Cichorium intybus (chicory), Cucumis melo (melon), Enterolobium schomburgkii (earpod wood), Persea americana (avocado), Terminalia catappa (olive bark tree), and Vigna unguiculata (asparagus bean var. A), showed only halos of S. mutans growth stimulation. The following species showed halos of S. mutans growth inhibition and stimulation: Solanum sessiliflorum (cocona), Ricinus communis (castor bean), and Psophocarpus tetragonolobus (winged bean), Cariniana micrantha (brown capuchin monkey), Hymenaea courbaril (locust tree), Parkia pendula (acacia male), Mucuna urens (cow-icht plant), Zygia cauliflora (jarandeua), Cucumis sativus (cucumber), Ormosia excelsa (horse-eye bean), Eugenia stipitata (araza), Vigna unguiculata (asparagus bean var. B), Buchenavia huberi (tanibuca), Dinizia excelsa (angelim-pedra), Morinda citrifolia (indian mulberry), Peltogyne paniculata (purple heart), Swartzia laevicarpa (saboarana), Acosmium nitens (taboarana), Campsiandra comosa (acapurana), Schizolobium amazonicum (paricá), Leucaena leucocephala (wild tamarind), Artocarpus heterophyllus (jackfruit) and Parkia multijuga (pinho-cuiabano). The seeds extracts of the following species showed significant removal of dental biofilm: Solanum sessiliflorum (cocona), Cariniana micrantha (brown capuchin monkey), Hymenaea courbaril (locust tree), Zygia cauliflora (jarandeua) and Mucuna urens (cow-icht plant), removing more than 41,6.107 cells. Seeds extracts of Parkia pendula (acacia male), Ricinus communis (castor bean), Cucumis sativus (cucumber) and Ormosia excelsa (tento-amarelo) removed between 37,6- 39,6.107 cells. The results allowed drawing a profile of species, among the 32, for possible future use in dentistry.